"Stop Resisting or You’re Gonna Get It Again": Police Use of Force in a Canadian Crime Reality Television Show - Pohl, Ethan (Canadian journal of criminology and criminal justice, 2022)
Extant research suggests that crime reality television advances biased narratives about offenders, police officers, and the nature of crime. This study contributes to the literature by investigating the prevalence, severity, and proportionality of police use of force in Under Arrest, a Canadian crime reality television show. Using a content analysis of all 65 Under Arrest episodes, research reveals that police use of physical force is portrayed in nearly half of vignettes, and over half of force used is excessive force. Logistic regression indicates that the racial composition of the suspect pool does not predict use of force when controlling for other relevant variables. However, suspect race is the strongest predictor of excessive force even when controlling for initial crime seriousness, gender, suspect intoxication, and weapon possession. Results indicate that Under Arrest contributes to law and order ideology by portraying police use of force as a necessary and justified tool for controlling crime committed by racialized suspects.